AVALIAÇÃO DO POTENCIAL AGRÍCOLA NOS DISTRITOS DO MUNICÍPIO DE CAMETÁ - PARÁ (REMUNOM, 2025)
Agricultural production is strongly influenced by soil conditions, which have been one of the main limiting factors for production. Techniques for identifying suitable areas based on soil information make it possible to define favorable environments for agricultural exploration, contributing to reducing the risks of environmental degradation. The objective of the study is to gather, map and make available information on agricultural suitability and contribute to the rational use of land in each of the districts of the municipality of Cametá. The methodology adopted was based on the recognition map of the high intensity of Cametá soils, which was digitized so that the analysis of agricultural suitability and soil typology could be done at the district level using the Qgis 3.24 software. As a result, it was found that only 35% of the territory of Cametá has a rural environmental registry, with emphasis on the district of Janua Coeli, where 60% of its area is registered in National Rural Environmental Registry System. The municipality has six types of soil, with a predominance of the Haplic Plinthosol, not suitable for cultivation, and the Yellow Latosol, with physical characteristics more suitable for farming. Regarding agricultural suitability, 31% of Cametá's lands are suitable for planting crops, 2% for pastures, 29% for crops adapted to floodplain areas and 38% are characterized as unsuitable for any agricultural crop or livestock, which corroborates the agro-extractivist and family profile of Cametá's farmers. It is concluded that, of the districts analyzed, Vila do Carmo has lands suitable only for environmental preservation, while Areião has soils favorable to the production of various agricultural crops. In this sense, environmental regularization is essential to guarantee technical assistance and credit to farmers in areas suitable for farming. Keywords: Agricultural Aptitude; Rural Environmental Registry; Amazonian Soils.